Mechanical Response of Applying Different Parameters On Negative Stiffness Honeycomb Structure - Takrouny, Abdalla Rabie; Tarlochan , Faris (International Journal of Integrated Engineering, 2023)
It has become apparent that negative stiffness behavior may have potential applications in vibration isolation mechanisms, vibro-acoustic dampening materials, and mechanical switches. Unlike traditional honeycombs, due to these properties, a negative honeycomb can absorb substantial amounts of mechanical energy whilst maintaining a stable stress. The force threshold under displacement loading was investigated of three variables applied on different models of negative-stiffness honeycomb (NSH) structures. The three variables are material applied, honeycomb unit cell, and beam thickness of the negative honeycomb structure. Accordingly, nine models were developed, and the three varied materials were assigned repeatably to each model and then force threshold were studied after validating the model. The Finite element analysis (FEA) for formed model was validated and shows force value of 289 N with an error of 5% compared to the referenced model. In the 4- unit cell model, the highest force threshold of approximately 240 N was noticed during loading phase at the beam thickness of 19.05 mm for both nylon 11 and 12 material. Finally, the force threshold of 550 N during loading and unloading phases was observed for nylon 6/6 material at beam thickness of 19.05 mm. The results obtained confirm the negative stiffness behavior on the models and shows that the force threshold applied is reduced comparing to forces required in the conventional honeycombs models.